PENGARUH PENERAPAN AKUNTANSI BERBASIS AKRUAL DALAM PELAPORAN KEUANGAN SEKTOR PUBLIK (YAYASAN PUNDI AMAL PEDULI KASIH 2022) - Fernisia, Mike; Siboro, Sony Fransisco; Ningrum, Paulina Putri; Dwiyanti, Salsabilla (Universitas Trilogi, 2024)
The main objective of this research is to find out how the application of accrual-based accounting in public sector financial reporting has influenced the foundation in particular. To do this, the author combines qualitative methodology with a literature review from previous research. The findings of this study show the significant impact of accrual-based accounting on improved transparency, application, and accuracy of financial statements in the public sector.Keywords: Accrual-based accounting; Accuracy; Financial statements; Transparency; Public sector